Brain connectivity moderated the effects of cognitive intraindividual variability on mobility in cognitively frail older adults - Wu, Jingyi; Chen, Jinyu; Wu, Juncen; Chan, Wayne Lap Sun; Yang, Yijian; Hsu, Chun Liang (Frontiers in Aging Neuroscience, 2025)
IntroductionCognitive frailty, defined by the coexistence of mild cognitive impairment and physical frailty, imposes greater risk of negative health consequences than either condition alone. Cognitive intraindividual variability (IIV), which reflects the extent of fluctuation in cognitive performance, is an early indicator of impaired cognition and mobility. To extend current understanding of the underlying neural mechanisms of increased IIV due to cognitive frailty, this study investigated the association between brain networks, IIV, and mobility.MethodsA total of 38 community-dwelling cognitively frail/non-cognitively frail older adults (CF and non-CF; n = 17 and n = 21, respectively) underwent clinical assessments including the Trail Making Test, Stroop Test, Timed Up and Go test (TUG), and resting-state functional magnetic resonance imaging. Dispersion across executive tests was computed to ascertain IIV (IIV-dispersion). Analysis of covariance was used to determine group differences in IIV-dispersion and functional network connectivity adjusted for functional comorbidities. Moderation models were constructed to investigate the role of functional neural networks in the association between IIV-dispersion and TUG performance.ResultsCompared to non-CF group, CF group exhibited greater IIV-dispersion (p = 0.042), lower within sensorimotor network (SMN) connectivity, and lower connectivity between the default mode network (DMN), fronto-executive network (FEN), and SMN (all p < 0.050). Further, regional DMN-FEN connectivity moderated the relationship between IIV-dispersion and TUG performance (R-sq = 0.427, p = 0.001) only among the CF.DiscussionGreater IIV-dispersion due to cognitive frailty may be underpinned by large-scale altered functional connectivity across networks. However, localized reconfiguration of DMN-FEN connectivity may uniquely represent adaptive compensatory processes by which mobility is protected against the detrimental impact of greater IIV-dispersion secondary to cognitive frailty.